2004
DOI: 10.1002/bjs.4588
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in the pathological assessment of malignant colorectal polyps

Abstract: Pathological assessment of malignant polyps varies between observers. Specialist pathologists appear to have a higher degree of consensus among themselves than with generalist pathologists with respect to T stage. The high interobserver variability with regard to histological grade of differentiated tumours is clinically irrelevant. However, variability in the assessment of angiolymphatic vessel invasion limits the value of this measurement for clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Accepted low-risk tumors are well to moderately differentiated T1 rectal cancers without lymphatic or vascular invasion [25]. However, evidence is not abundant, and inter-and intra-observer variability in scoring each of those items is not to be underestimated [26][27][28]. This study again questions the reproducibility and predictive value of basic histopathologic staging.…”
Section: Discussionmentioning
confidence: 86%
“…Accepted low-risk tumors are well to moderately differentiated T1 rectal cancers without lymphatic or vascular invasion [25]. However, evidence is not abundant, and inter-and intra-observer variability in scoring each of those items is not to be underestimated [26][27][28]. This study again questions the reproducibility and predictive value of basic histopathologic staging.…”
Section: Discussionmentioning
confidence: 86%
“…They noted that specialist pathologists had a higher degree of consensus among themselves than with generalist pathologists with respect to T stage. High interobserver variability was also seen with regard to histological grade and angiolymphatic invasion [22]. Others have reported interobserver variability and difficulties in the accurate assessment of lymphatic invasion.…”
Section: Diagnosing the Malignant Adenomamentioning
confidence: 88%
“…For CRC, studies have shown fair to moderate agreement among pathologists with respect to histologic type 42,43 and histologic grade. 44 Variation in histologic grading by pathologists exists in part because of the lack of a universally accepted standardized grading system. Also, the frequency of grading varies by histologic type and cancer site.…”
Section: Discussionmentioning
confidence: 99%